Mechanical, electronic and optical properties of K2TeX6 (X=Cl, Br, I) perovskite derivatives using density functional theory. (1st March 2021) - Du, Xue; He, Dafang; Mei, Huayue; Liu, Yuqing; Cheng, Nanpu
Abstract: In this study, the elastic, electronic, and optical properties of cubic, tetragonal and monoclinic K2 TeX6 (X = Cl, Br, I) perovskite derivatives are investigated using first-principles calculations. The results reveal that different space groups have a minor influence while the atomic number of X has a significant influence on the physical properties of these perovskite derivatives. In their crystal structures, X and K atoms form X–K ionic bond, while X and Te atoms form X–Te ionic bond with more covalent components. For K2 TeBr6 perovskite derivatives within the three different space groups, the close Br–Te bond lengths slightly decrease as the symmetry decreases. However, for the monoclinic K2 TeX6 (X = Cl, Br, I) perovskite derivatives, as the atomic radius of X increases, the X–Te bond lengths increase with the decrease in covalent bond components. All the K2 TeX6 (X = Cl, Br, I) perovskite derivatives exhibit obvious elastic anisotropy. The monoclinic K2 Te2 I6 perovskite derivative is brittle, but K2 TeX6 (X = Cl, Br) perovskite derivatives are ductile. In the electronic structures of the perovskite derivatives, the top valence bands are primarily contributed by X- p (Cl-3 p, Br-4 p, or I-5 p ) and Te-5 s orbits, and the bottom conduction bands are dominated by Te-6 p orbit. The effective masses and carrier mobilities exhibit distinct anisotropy due to the anisotropic crystal structures. As the atomic number of X increases, the effective masses of electrons and holes gradually decrease, while the carrier mobilities increase. Especially, the higher carrier mobilities of monoclinic K2 Te2 I6 perovskite derivative are caused by its smaller effective masses. The K2 TeX6 (X = Cl, Br, I) perovskite derivatives exhibit excellent dielectric functions and absorption coefficients in the visible and ultraviolet regions. Highlights: Halogen atoms X have a great influence on physical properties of K2 TeX6 crystals. Carrier effective masses decrease while carrier mobilities increase for X = Cl, Br, I. Electronic transitions from X- p to Te-6 p orbits dominate optical properties of K2 TeX6 . K2 Te2 X6 have good absorption coefficients in the visible-ultraviolet regions.